Migrating from Drupal to Backdrop - Tomlinson, Todd (Apress : Imprint: Apress, 2015)
Migrate an existing Drupal 6 or 7 website to Backdrop and discover why you should consider using Backdrop when building a new website. You'll learn what Backdrop is, how to install and configure Backdrop, and create and manage content. Migrating from Drupal to Backdrop focuses on the user who is responsible for building, maintaining, and managing an organization's website and who is interested in Backdrop's ability to meet their site's requirements. There is a major shift in the open source CMS market and Backdrop is emerging as a significant force. The Drupal team's decision to rebuild Drupal 8 on Symfony has many developers and organizations in a quandary - do you learn a whole new framework and undertake the effort of migrating to Drupal 8, stay on Drupal 7 which will at some point be officially unsupported, or adopt Backdrop as their go-forward strategic platform? There is also a large mid-market that may not have the ability to scale up with the skills required to support Drupal 8 (Symfony), making Backdrop a viable and attractive alternative. By reading this book, you will: Understand why you should use Backdrop and the power of the platform Quickly build confidence in your ability to use Backdrop Gain the knowledge necessary to build, deploy, and manage web sites of moderate complexity on Backdrop Understand the process for migrating a Drupal 6 or 7 site to Backdrop What You Will Learn: What Backdrop is and why you should use it How to install a basic Backdrop web site from scratch How to create content in your new Backdrop web site How to install and configure modules How to migrate a Drupal 6 site to Backdrop How to migrate a Drupal 7 site to Backdrop Who This Book Is For: < This book is for technical users who need to use Backdrop to create websites using the platform or to manage existing content, as well as developers who are new to the Backdrop platform. The book is also targeted at organizations that currently use Drupal 6 or 7 and who wish to remain on the base architecture of those platforms as they move forward on Backdrop.